CURRENT STATE OF ACCELERATED ENQUIRY - EVOLUTION OR DEGRADATION OF THE PROCEDURAL FORM - Girko, S.I. (International Journal of Psychosocial Rehabilitation, 2020)
ABSTRACT–The article analyzes the legal regulation of inquiry in an abbreviated form, set forth in Chapter 32.1 of the CPC of the Russian Federation, and the practice of inquiry in an abbreviated form on the territory of Russia, on the basis of the positions expressed in the scientific literature by processional scientists, and also through the prism of international standards of police inquiry. It concludes that, despite the discussions of scientists, the model of accelerated inquiry, introduced in the CPC of the Russian Federation, generally meets the requirements, and the organizational measures of the Ministry of Internal Affairs will allow spreading the rule of law.